The sacraments in the declarations and decrees of II Archdiocesan Synod in Katowice - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2018)
In the years 2015-2016 in Katowice took place II Archdiocesan Synod. After its completion declarations and decrees was issued. Some of these concern issues related to the sacraments. Synodal norms raise very important pastoral problems of baptism, confirmation, Eucharist, penance, anointing of the sick, sacrament of order and marriage. Many of decrees concern preparation for the reception sacraments. This publication shows archdiocesan synodal law and interprets it.